Proceedings of the 2014 International Conference on Generative Programming: Concepts and Experiences 2014
DOI: 10.1145/2658761.2658773
|View full text |Cite
|
Sign up to set email alerts
|

Optimization by runtime specialization for sparse matrix-vector multiplication

Abstract: Runtime specialization optimizes programs based on partial information available only at run time. It is applicable when some input data is used repeatedly while other input data varies. This technique has the potential of generating highly efficient codes.In this paper, we explore the potential for obtaining speedups for sparse matrix-dense vector multiplication using runtime specialization, in the case where a single matrix is to be multiplied by many vectors. We experiment with five methods involving runtim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
0
1
0
1
Order By: Relevance
“…Çalışmamızda CSR tabanlı SpMV işleminin maliyeti düşük bir şekilde hızlandırılması üzerine odaklandık. Matris elemanlarının yeniden sıralanması ve CSR'den daha sofistike saklama formatı kullanılmasıyla SpMV işlemini belirgin şekilde hızlandırmak mümkün olabilir (örneğin [1,6,7,20,24,25] [23,32]. Bu çalışmalarda sunulan teknikler vasıtasıyla vals ve cols dizileri de sıkıştırılabilir, fakat ön işleme safhasına bu dizilerin de eklenmesi ön işlemenin maliyetini artıracağı için bu yaklaşımları kullanmadık.…”
Section: İlgili çAlışmalarunclassified
“…Çalışmamızda CSR tabanlı SpMV işleminin maliyeti düşük bir şekilde hızlandırılması üzerine odaklandık. Matris elemanlarının yeniden sıralanması ve CSR'den daha sofistike saklama formatı kullanılmasıyla SpMV işlemini belirgin şekilde hızlandırmak mümkün olabilir (örneğin [1,6,7,20,24,25] [23,32]. Bu çalışmalarda sunulan teknikler vasıtasıyla vals ve cols dizileri de sıkıştırılabilir, fakat ön işleme safhasına bu dizilerin de eklenmesi ön işlemenin maliyetini artıracağı için bu yaklaşımları kullanmadık.…”
Section: İlgili çAlışmalarunclassified
“…Our method is based on the fundamental idea of loop unrolling. We had previously shown that loop unrolling provides speedup for SpMV, but we had done that for formats that re‐arrange matrix data. Another paper that investigates loop unrolling for SpMV is by Mellor‐Crummey and Garvin .…”
Section: Related Workmentioning
confidence: 99%